Social Media Problems On Child Intelligence At Sdn 11 Lolong - Santia, Letri; Asyifa Aulia, Nurul (The Future of Education Journal, 2023)
The purpose of this study was to examine the use of social media by students in elementary schools, the impact arising from the use of social media for elementary school students, and the role of school policies on the use of social media. This study uses a qualitative descriptive research method with a case study approach. The subjects of this study were students, teachers, principals, and parents of students. Data collection methods consist of observation, interviews, and documentation. Data analysis by way of reduction, data presentation, and drawing conclusions. The results showed that (1) students used social media for actualization and visualization, (2) the frequency of accessing social media was available on the ownership of gadgets and facilities, (3) the positive impact of using social media was to facilitate communication between students and teachers; as a learning tool and looking for learning reference sources. On the other hand, the negative impact of using social media is students' addiction to negative content. (5) The role and policies of schools on the use of social media for students cannot be dammed by prohibitions, (6) but the policies of principals who follow current educational developments are allowed to use such use by emphasizing the role of the teacher as the main object in the supervision and control efforts within the school. and outside the classroom during school time